Cooperation between local communities and the civil protection in overcoming the COVID-19 crisis - Prebilič, Vladimir (Annales. Series historia et sociologia, 2021)
The unprecedented strike of the COVID-19 pandemic and the resulting aftermath pose profound challenges for local governments, from managing responses, to an unknown crisis, to ensuring the safety of citizens in the midst of extreme uncertainty. The paper discusses the management of the COVID-19 crisis, focusing on the cooperation between Slovenian municipalities and the established civil protection system. Civil protection and emergency preparedness to cope with natural, technological and other disasters is a key component of any local community. The authors examine the normative framework of the civil protection system in the Republic of Slovenia and offer insights into the results of the first empirical study to evaluate civil protection regulations, emergency response, and operations at the municipal level during the response to the COVID-19 crisis.
Keywords: Civil defense; Civilna zaščita; COVID-19; Crisis management; Epidemics; Epidemije; Krizno upravljanje; lokalna skupnost; Municipalities; Občine; pandemije